Posttranslational microtubule modification alters podocalyxin-trafficking in epithelial cells - Gorek, Lena-Sophie; Trauth, Dominik; Kamm, Natalia; Schiffke, Lana Sophie; Zerbian, Carlotta; Mende, Lina-Marie; Jacob, Ralf (Frontiers in Cell and Developmental Biology, 2025)
Epithelial polarization is characterized by separation of the plasma membrane into an apical and a basolateral membrane domain. This morphology is verified by cytoskeletal organization that stabilizes the cellular architecture and provides specific tracks for correct polarized cargo delivery. Here, we studied effects of tubulin (de-) tyrosination on epithelial polarization and apical trafficking of the membrane protein podocalyxin/gp135. Therefore, tubulin tyrosine ligase (TTL), the enzyme that adds tyrosine to the carboxy terminus of detyrosinated α-tubulin, was knocked out or overexpressed in MDCK cells. TTL-knockout alters podocalyxin-expression and -glycosylation, which was compensated by overexpression or rescue of TTL. Moreover, intracellular interaction of podocalyxin with ezrin was reduced in the absence of TTL. This suggests that posttranslational microtubule-modification can modulate maturation and function of the glycoprotein. We used the SNAP-tag system to examine membrane delivery of podocalyxin and found atypical spreading of the newly synthesized glycoprotein all over the apical membrane and an altered subapical architecture of microtubules in cells with an elevated content of detyrosinated α-tubulin. Our studies suggest that intracellular trafficking of podocalyxin can be controlled by TTL-dependent posttranslational modification of microtubules in polarized epithelial cells.